Autonomous and democratic management: a study on municipal public schools of Santa Catarina state - Sulivan Desirée Fischer; Maria do Carmo Lessa Guimarães (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
The paper analyzes the factors that contribute to and / or constrain the autonomous and democratic management from the provision mechanisms for the position of school director, training and experience of this manager on the performance of the duties. The autonomous and democratic management is an attribute of the school management stated in the LDB/96 favoring the expansion of the participation in school decision-making process, as well as the transfer of the decision-making power to the school level, with allocation of resources of different nature. Were investigated eighteen municipal elementary schools in six pole municipalities of the State's mesoregions, being one small size school, one middle size school and one big size school in each of these counties. The research concludes that the direct election for the position of school director, a mechanism that, according to some authors, contributes to broaden participation in school management, has not been introduced to all schools of Santa Catarina state. Training and experience seem favorable to the performance of the director's duties. However, it seems not to generate a differential to the institutionalization of autonomous management. The research points to challenges to be overcome in the search for the institutionalization of the democratic logic that favors discussions around the directive issue.